Sinusoidal Endothelial Cell Progenitor Cells Promote Tumour Progression in Patients with Hepatocellular Carcinoma - Ya-xing Feng; Wei Li; Xu-dong Wen; Ning Zhang; Wei-hui Liu; Zhan-yu Yang (Hindawi Limited, 2020)
Objective. As sinusoidal endothelial cell progenitor cells (SEPCs) play a significant role in liver regeneration, it is necessary to elucidate whether SEPCs participate in tumour progression of hepatocellular carcinoma (HCC). Methods. A total of 45 patients with primary HCC who underwent liver resection were included in this study. The liver tumours were removed from the patients, and partial tissues were prepared to identify SEPCs through double staining of CD133/CD45 and CD133/CD31 at the same location. Blood samples were collected to examine liver function parameters and tumour markers. The demographics and clinicopathological characteristics of the patients were collected for correlation analysis with SEPCs. Results. SEPCs were observed in several blood vessels within the HCC nodules of all 45 patients, but no SEPCs were detected in the tumour-adjacent tissues. The number of SEPCs was correlated with the expression levels of HCC tumour markers α-fetoprotein (AFP) and CA199. There was a positive correlation between the expression of SEPC markers and diameter of HCC tumours in differently differentiated specimens (P<0.01). The expression levels of SEPC markers were significantly higher in patients with poorly differentiated HCC than in patients with moderately and highly differentiated HCC (P<0.05). Conclusions. SEPCs are closely associated with HCC progression; therefore, SEPCs may be considered potential prognostic and metastatic biomarkers and therapeutic candidates for HCC.